WIRELESS GENERATIONS OF ELECTRONIC COMMUNICATIONS: TECHNOLOGICAL POSSIBILITIES - Кузьмін, Андрій; Цибульов, Роман; Смоляр, Віктор; Івко, Сергій (Modern engineering and innovative technologies, 2024)
The article examines the evolution of mobile networks from 1G to modern fifth-generation systems and highlights important aspects of the "big data" concept. The authors analyse the growing need for processing large volumes of data in the future 6G mobile